2005
DOI: 10.1677/jme.1.01807
|View full text |Cite
|
Sign up to set email alerts
|

Rab coupling protein (RCP): a novel target of progesterone action in primate endometrium

Abstract: Acquisition of functional receptivity by the endometrium is assumed to be effected by progesterone-dependent expression and repression of several genes during the implantation window in a menstrual cycle. In the present study, we employed differential display (DD) reverse transcription-polymerase chain reaction (RT-PCR) to identify progesterone-dependent gene/gene fragments that are differentially expressed during the peri-implantation phase in receptive and nonreceptive endometria, obtained from fertile and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…To investigate whether HOXA10 is under the regulation of progesterone in primate endometrium, its expression was studied in the endometria of animals treated with onapristone. We have earlier shown that onapristone, at the specified doses in bonnet monkey, does not affect the hypothalamus-pituitary-ovarian axis but blocks implantation in the bonnets (Katkam et al 1995) and the expression of some progesterone-regulated genes is also altered (Puri et al 2000, Sachdeva et al 2001, Patil et al 2005. In the present study, we found that blocking progesterone actions (by onapristone treatment) lead to suppression of HOXA10 mRNA and protein expression in the endometrium.…”
Section: Discussionsupporting
confidence: 56%
“…To investigate whether HOXA10 is under the regulation of progesterone in primate endometrium, its expression was studied in the endometria of animals treated with onapristone. We have earlier shown that onapristone, at the specified doses in bonnet monkey, does not affect the hypothalamus-pituitary-ovarian axis but blocks implantation in the bonnets (Katkam et al 1995) and the expression of some progesterone-regulated genes is also altered (Puri et al 2000, Sachdeva et al 2001, Patil et al 2005. In the present study, we found that blocking progesterone actions (by onapristone treatment) lead to suppression of HOXA10 mRNA and protein expression in the endometrium.…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, it is now clear that the FIPs are critical regulators of multiple endosomal-recycling processes (Figure 2). They have also been shown to function in several crucial cellular physiological processes such as cell division, cell migration, responses to insulin, memory processes, immune and inflammatory responses, water reabsorption, fertility, retinal cell development and various human cancers [16,24,27,28,[32][33][34][35][36][37][47][48][49][50]. This repertoire of FIP functions is everexpanding and as many of these cellular processes are disease associated, it identifies the FIPs as potential targets for therapeutic intervention in the treatment of human diseases in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclicity and the hormonal profiles of the animals have been reported previously (Patil et al 2005).…”
Section: Methodsmentioning
confidence: 97%